Infalling clouds on to supermassive black hole binaries - II. Binary evolution and the final parsec problem - Goicovic, Felipe G. (2017)
The formation of massive black hole binaries (MBHBs) is an unavoidable outcome of galaxy evolution via successive mergers. However, the mechanism that drives their orbital evolution from parsec separations down to the gravitationalwave dominated regime is poorly understood, and their final fate is still unclear. If such binaries are embedded in gas-rich and turbulent environments, as observed in remnants of galaxy mergers, the interactionwith gas clumps (such as molecular clouds)may efficiently drive their orbital evolution. Using numerical simulations, we test this hypothesis by studying the dynamical evolution of an equal mass, circular MBHB accreting infallingmolecular clouds.We investigate different orbital configurations,modelling a total of 13 systems to explore different possible impact parameters and relative inclinations of the cloud-binary encounter. We focus our study on the prompt, transient phase during the first few orbits when the dynamical evolution of the binary is fastest, finding that this evolution is dominated by the exchange of angular momentum through gas capture by the individual black holes and accretion. Building on these results, we construct a simple model for evolving an MBHB interacting with a sequence of clouds, which are randomly drawn from reasonable populations with different levels of anisotropy in their angular momenta distributions. We show that the binary efficiently evolves down to the gravitational wave emission regime within a few hundred million years, overcoming the 'final parsec' problem regardless of the stellar distribution.